1973
DOI: 10.1080/14640747308400340
|View full text |Cite
|
Sign up to set email alerts
|

Learning 10000 pictures

Abstract: Four experiments are reported which examined memory capacity and retrieval speed for pictures and for words. Single-trial learning tasks were employed throughout, with memory performance assessed by forced-choice recognition, recall measures or choice reaction-time tasks. The main experimental findings were: (1) memory capacity, as a function of the amount of material presented, follows a general power law with a characteristic exponent for each task; (2) pictorial material obeys this power law and shows an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
646
2
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 871 publications
(678 citation statements)
references
References 18 publications
23
646
2
7
Order By: Relevance
“…al., 2005)] and some of them also account for the enormous memory capacity observed by Standing (1973) (Bogacz et al, 2001;Bogacz and Brown, 2003). Here, we propose a particularly simple neural system, endowed with conservative Hebbian synaptic plasticity, capable of accounting for the monkey psychophysics experiments we present and for the related findings of Standing.…”
Section: Network Model (Theory)mentioning
confidence: 77%
See 3 more Smart Citations
“…al., 2005)] and some of them also account for the enormous memory capacity observed by Standing (1973) (Bogacz et al, 2001;Bogacz and Brown, 2003). Here, we propose a particularly simple neural system, endowed with conservative Hebbian synaptic plasticity, capable of accounting for the monkey psychophysics experiments we present and for the related findings of Standing.…”
Section: Network Model (Theory)mentioning
confidence: 77%
“…How can the traces preserved in the synapses distinguish first from second presentations of a stimulus [as found in humans by Standing (1973) and by ourselves, above, in monkeys], without delay activity? Figure 5A (red curve) presents stationary state spike rates during stimulation, averaged over the active neurons responsive to each stimulus, after learning 200 stimuli, as a function of stimulus number; no.…”
Section: Familiarity Recognition Signal and Readoutmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of the currently attended object (or very recently attended objects), scene memory is proposed to be schematic, retaining the gist of the scene and the spatial layout of the scene (i.e., the spatial configuration of surfaces and object positions), but not retaining episodic visual details from local objects. Because these views hold that no robust representation of the visual details of a scene is constructed during online viewing, researchers have necessarily concluded that high capacity, robust LTM in the picture memory literature (e.g., Nickerson, 1968;Standing, 1973) must have been based on the retention of abstract scene gist or layout information (Chun, 2003;Simons, 1996;Simons & Levin, 1997). Hollingworth and Henderson (2002) sought to resolve the apparent discrepancy between claims of visual transience in the change blindness literature and evidence of high capacity, robust memory for pictures.…”
mentioning
confidence: 99%